HR TRENDS AND TENDENCIES IN HUNGARY IN THE LIGHT OF THE EXPERIENCES OF THE LATEST CRANET SURVEY 2021 - POÓR, József; JARJABKA, Ákos; KAROLINY, Zsuzsa; BALOGH, Gábor; GALAMBOSNÉ TISZBERGER, Mónika; KŐMÜVES, Zsolt Sándor; SZABÓ, Katalin; SZABÓ-SZENTGRÓTI, Gábor (Studia Universitatis Babeș-Bolyai Oeconomica, 2022)
The regime change in 1989 marked a significant milestone in the development of human resource (HR) management in Hungary. Changes in the legal, institutional and ownership environment placed significantly different demands on the HR work of companies and institutions. It has become very important for organizations to have access to comparative HR data with other organizations related to HR activities. The Cranet international HR university non-for-profit research network, founded in 1989 in Cranfield, England, has a long tradition in this field. Hungarian researchers have participated in Cranet’s international HR research on four occasions so far. In this article, we aim to present the main features of the Cranet HR research in Hungary in 2021. We review the findings and noteworthy results of the research. Where possible, we compare it with relevant data from the 2014-2016 survey. JEL classification: M50, M51, M52, M53, M54